1996
DOI: 10.3354/meps141037
|View full text |Cite
|
Sign up to set email alerts
|

Growth, filtration and respiration in the mussel Mytilus edulis:no evidence for physiological regulation of the filter-pump to nutritional needs

Abstract: The specific growth rate of blue mussels Mytilus edulis fed Rhodomonas sp. algal cells in laboratory experiments increased with increasing food concentration to obtain a maximum value of about 9 . 5 % d-', irrespective of a relatively h~g h concentration of silt (5 mg 1.' ) added to the water. Ltkewise, the net growth efficiency increased with the spec~fic growth rate to a maximum value of about 75%. Measurements of the relationship between respiration and growth showed that the energy cost of growth constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(111 citation statements)
references
References 17 publications
8
100
2
1
Order By: Relevance
“…As in previous investigations (Navarro & Iglesias 1993, Urrutia et al 1996, Navarro & Widdows 1997, and in contradiction of some scientists who reject the concept of physiological regulation of feeding (Clausen & Riisgard 1996, Jørgensen 1996, we found in the present experiments that cockles increase processing rates when faced with an increase in particulate matter associated with a decrease in the quality of the suspension. Regulation of ingestion rate by means of keeping high rates of rejection coupled to high rates of filtration leads to a significant increment in the organic fraction of ingested matter, which, in turn, enhances the efficiency of digestive processes.…”
Section: Discussioncontrasting
confidence: 46%
“…As in previous investigations (Navarro & Iglesias 1993, Urrutia et al 1996, Navarro & Widdows 1997, and in contradiction of some scientists who reject the concept of physiological regulation of feeding (Clausen & Riisgard 1996, Jørgensen 1996, we found in the present experiments that cockles increase processing rates when faced with an increase in particulate matter associated with a decrease in the quality of the suspension. Regulation of ingestion rate by means of keeping high rates of rejection coupled to high rates of filtration leads to a significant increment in the organic fraction of ingested matter, which, in turn, enhances the efficiency of digestive processes.…”
Section: Discussioncontrasting
confidence: 46%
“…The total length of all groynes in this area was estimated from nautical charts, and the total abundance of sublittoral M. edulis was calculated. Total filtration performance was calculated using the filtration rates for M. edulis from the literature range from 1.5 to 3.0 l h À1 individual À1 (Mølenberg and Riisgård, 1979;Famme et al, 1986;Clausen and Riisgård, 1996).…”
Section: Data Collection and Processingmentioning
confidence: 99%
“…Several experiments conducted both in the field (Fréchette and Bourget 1985;Fréchette et al 1989;Dolmer 2000a, b) and in flumes (Wildish and Kristmanson 1984;Butman et al 1994) have shown that suspension-feeding animals, including blue mussels, are able to deplete seston from the near-bed layer. This indicates that at least some sections of a mussel bed may be food-limited and a change in near-bed mixing may therefore affect individual growth, especially in the downstream parts of mussel beds (Fréchette and Bourget 1985;Fréchette et al 1989;Clausen and Riisgård 1996). Since blue mussels may close their valves in response to tactile stimuli from shorecrabs and other larger motile species, the mere presence of these animals will influence the filtration activity and hence the growth of these zoobenthic filter feeders.…”
Section: Impact On Mussel Growthmentioning
confidence: 99%